THE CORRELATION BETWEEN STUDENTS’ SELF-CONFIDENCE AND SPEAKING ABILITY AT TENTH GRADE STUDENTS OF SMAN 5 KABUPATEN TANGERANG IN ACADEMIC YEAR 2018/2019 - Iin Seftiani; Agus Mulyana; Tenia Ramalia (JIPIS, 2018)
AbstractThis research was conducted at SMAN 5 Kabupaten Tangerang. The aim of this research to whether there was the correlation between students' self-confidence and speaking ability. The population of this research was the tenth grade students at SMAN 5 Kabupaten Tangerang. The samples are 40 students of X Social 2. This research used correlational research. The researcher used Questionnaire and speaking test to collect data. Based on test hypotheses, it has been found that the correlation coefficient between students’ self-confidence and speaking ability is 0,460. It shows that the variable has correlation from 40 students which their speaking ability is influenced by their self-confidence. The result of hypotheses is alternative hypotheses (Ha) is accepted and the null hypotheses (Ho) is rejected. In addition, the research was seen if the students’ self-confidence and speaking ability have a significant positive correlation between students’ self-confidence and speaking ability at tenth grade of SMAN 5 Kabupaten Tangerang in Academic Year 2018/2019.Keywords: Self-confidence, SMAN 5 Kabupaten Tangerang, speaking abilityAbstrak           Penelitian ini dilakukan di SMAN 5 Kabupaten Tangerang. Tujuan penelitian ini adalah untuk mengetahui apakah ada hubungan antara kepercayaan diri dan kemampuan berbicara siswa. Populasi dalam penelitian ini adalah siswa kelas X di SMAN 5 Kabupaten Tangerang. Sampelnya terdiri dari 40 siswa X IPS 2. Penelitian ini menggunakan penelitian korelasional. Peneliti menggunakan Kuesioner dan tes berbicara untuk mengumpulkan data. Berdasarkan uji hipotesis, telah ditemukan bahwa koefisien korelasi antara kepercayaan diri siswa dan kemampuan berbicara adalah 0,460. Ini menunjukkan bahwa variabel tersebut memiliki hubungan dari 40 siswa yang kemampuan berbicaranya dipengaruhi oleh kepercayaan diri mereka. Hasilnya adalah hipotesis alternatif (Ha) diterima dan hipotesis nol (Ho) ditolak. Selain itu, penelitian ini dilihat apakah kepercayaan diri siswa dan kemampuan berbicara memiliki hubungan positif yang signifikan antara kepercayaan diri dan kemampuan berbicara siswa di kelas sepuluh SMAN 5 Kabupaten Tangerang pada Tahun Akademik 2018/2019.Kata Kunci: kemampuan bicara, kepercayaan diri,  SMAN 5 Kabupaten Tangerang